The Chinese dream: challenges and impacts for China's foreign policy - Sousa, Carolina Ribeiro de (2021)
The Chinese Dream was first introduced by Xi Jinping in 2012. Since then, the concept is being used as a common goal of the nation, serving as a way of increasing nationalism inside China, as well as drawing legitimacy to the CCP. So, the Chinese Dream is usually perceived as more of a national then international concept. However, the concept is often used internationally as well, when addressing other countries: terms such as the "African Dream" and the "World Dream" started to appear in speeches delivered by Chinese Leaders, standing as a soft power tool. Often, the dream is portrayed as a peaceful concept and is used to relate to other nations. The concept requires, as many times emphasized by many Chinese leaders, a peaceful world and good external relations, especially regionally. But the contradiction between this need and the increasing pressure of the population to defend Chinese interests abroad and the dependence of CCP's legitimacy on the realization of the dream may cause a conflict of interests within the concept. So, in order to understand the divergent and converging points of the international and national dimension of the Chinese Dream, and further answer the question "how does the Chinese Dream impact Chinese Foreign Policy", the research analysis both national and international discourses delivered by the CCP leaders and related to the concept. The aim is to understand the contradiction and obstacles of the concept and relate them to the implications they have for Chinese foreign policy.